Stanowisko delegacji Stanów Zjednoczonych na Konferencji Monetarnej i Ekonomicznej w Londynie (12 czerwca-27 lipca 1933) - Matera, Paulina (Acta Universitatis Lodziensis. Folia Historica, 2002)
October 1929 is recognised as the beginning of the Gre at Depression. On the last days of this month there was a serious crash on the New York’s Stock. Since then, the economic situation of most countries of the world has been getting worse. Soon it became certain that all the countries had to co-operate to cope with difficulties such as unemployment, drop of the prices and barriers in the international trade. That is why in July 1932 it was decided to call the conference in which all the countries of the world would take part to deal with the main problems of the depression and to decide about the means of co-operation. The conference began on the 12th June 1933 in London. The government of United States sent its delegation with the Secretary of State – Cordell Hull. But the new president Franklin Delano Roosevelt had just started his program of New Deal - an attempt to finish the depression in his own country. In order to achieve this aim he had resigned the gold standard for dollar and he decided to concentrate on home affairs. He had known that interference of United States in European affairs is not popular among the public opinion of his country. That is why he told American delegation that the main task for them was to negotiate the trade treaties based on „the most favoured nation” clause and the better condition for American export. Till the beginning of the conference, many difficult problems between the United States and Europe were unsolved. One of the most important was the problem of war debts which European countries wanted to renegotiate. There was still hope that United States would lead world to the prosperity again, but during the conference it appeard to be impossible. The critical point of the debates was on 5th July. American delegation announced the message of president Roosevelt that his government was not interested in stabilisation of dollar and found it unuseful. Many delegations, particularly French for which this problem was essential, wanted to stop conference immediately. But it continued till 27th July and it brought no important results or settlements. The collapse of the conference was the great disappointment to the isolation policy of the United States and it caused lack of confidence and proved that there was no will of co-operation between countires against the results of the Great Depression.